Audit Quality in the Digital Era: A Delphi-Based Study on Factors Influencing Remote Auditing - Edwy, Ferby Mutia; Muhammad, Muhammad; Purnamasari, Fitri; Anugrahani, Inanda Shinta; Asmira, Zainah; Farida, Inur (Dinasti Publisher, 2026)
This study aims to identify factors that influence audit quality in remote auditing. The study was conducted using a two-round Delphi study, involving 31 experts, including lecturers, government auditors, and public accounting firm auditors. This study successfully reached a consensus on four main dimensions that influence remote audit quality, namely data, technology, human resources, and regulations. The results show that audit evidence collected through remote auditing has a relatively lower level of confidence compared to audits conducted in person. In addition, the absence of specific regulations is a major challenge, particularly regarding the reliability of audit evidence, data security, and the limitations of physical observation. This condition emphasises the need for clear regulations regarding the collection, storage, and verification of digital audit evidence so that remote audits remain in line with the principles of accountability and transparency. The findings of this study have practical implications for regulators in formulating remote audit policies and for auditors in adjusting relevant audit procedures.